British infantry battalion commanders in the First World War - Hodgkinson, Peter E. 1953- (Ashgate studies in First World War history, 2015)
Recent studies of the British Army during the First World War have fundamentally overturned historical understandings of its, yet the chain of command that linked the upper echelons of GHQ to the soldiers in the trenches remains poorly understood. In order to reconnect the lines of communication between the General Staff and the front line.